Right ventricular function in patients with pulmonary hypertension; the value of myocardial performance index (Tei index) measured by tissue Doppler imaging - Ibrahim, Abdullah; Mohammad, Ghazwan (Latakia University Journal -Medical Sciences Series, 2018)
Background: Identifying the most sensitive markers of RV dysfunction is of immense importance in daily clinical practice in the patients with pulmonary hypertension, and Myocardial performance index (tei index) is used to estimate both systolic and diastolic function of the right ventricle, the value of this index correlates; to IVRT, IVCT, and ET. Objectives: 1- To validate the accuracy of MPI as an easy and fast surrogate instead of conventional methodology assessment of the right ventricular dysfunction in patients with pulmonary hypertension. 2- Discussing the advantages of calculating the latter index by tissue doppler imaging versus conventional Doppler method. 3- Looking for an easy and accurate method to detect early stages of right ventricular dysfunction in cases of pulmonary hypertension, in which the function appear to be normal. Methods and results: We studied series of 64 patients (men and women) with (pulmonary hypertension) divided into three age groups and compared with 47 healthy age matched volunteers as a control group. We selected subjects from Tishreen university hospital, Lattakia over the year 2016. The MPI has been derived from pulse and tissue Doppler. Systolic s wave and IVRT have been derived from tissue Doppler imaging. Finally, TAPSE has been obtained from M-mode echocardiography. Bland–Altman analysis showed very good agreement between MPI and tMPI in patients (the mean difference was - 0.07, absolute difference -0.38 to 0.24; 95% intervals of agreement). A weak positive correlation was found between MPI Doppler and RVSP (mmHg) (r=0.18، p=0.05) and TRV (m/s)( r=0.18، p=0.05), and negative correlation with TAPSE (mm) (r=-0.21، p=0.03). A stronger positive correlation was found between tMPI and RVSP (mmHg) (r=0.28، p=0.02) and TRV (m/s) (r=0.29، p=0.02). Conclusion: from our patient, we found that tei index have a good correlation with pulmonary hypertension, and could reveal myocardial dysfunction before the developing of frank right ventricular failure. The assessment could be done with conventional or tissue method, even though the tissue imaging is little more preferred. Nevertheless, using both methods can increase the index value. وظيفة البطين الأيمن في مرضى ارتفاع التوتر الرئوي ؛ قيمة مشعر الأداء القلبي (Tei index) بطريقة التصوير بالدوبلر النسيجي مقدمة: يعد تحديد المشعرات الأكثر حساسية لسوء وظيفة البطين الأيمن على درجة عالية من الأهمية في الممارسة السريرية اليومية في مرضى ارتفاع التوتر الرئوي. و يستعمل مشعر الأداء القلبي (Tei index) لتقدير الوظيفة الانقباضية والانبساطية معا للبطين الأيمن، و ترتبط قيمة هذا المشعر بزمني الاسترخاء و الانقباض متساوي الحجوم و بزمن القذف البطيني. هدف البحث: 1- إثبات أن مشعر الأداء القلبي بديل سهل و سريع للمنهجية التقليدية في تقدير سوء وظيفة البطين الأيمن في مرضى ارتفاع الضغط الرئوي. 2- مناقشة ميزات حساب المشعر السابق بطريقة التصوير بالدوبلر النسيجي على الطريقة التقليدية بالدوبلر النبضي. 3- الكشف الباكر عن سوء وظيفة البطين الأيمن في حالات ارتفاع الضغط الرئوي و التي تبدو فيها الوظيفة البطينية محفوظة. مواد البحث و نتائجه: شملت الدراسة 111 شخصا منهم 47 شاهدا متطوعا من الأصحاء من الرجال و النساء و 64 مريضا (بارتفاع الضغط الرئوي) تمت مقارنتهم مع مجموعة الشاهد المماثلة لهم بالفئة العمرية بعد تقسيمهم إلى ثلاث فئات عمرية و ذلك من المراجعين لمستشفى تشرين الجامعي باللاذقية خلال عام 2016 م. تم اشتقاق مشعر الأداء القلبي بكل من الدوبلر النبضي التقليدي و الدوبلر النسيجي و أيضا حساب الموجة الانقباضية S و زمن الاسترخاء متساوي الحجوم IVRT بالدوبلر النسيجي و أخيرا قياس الانزياح الانقباضي لمستوى حلقة مثلث الشرف TAPSE بالإيكو وحيد البعد. وجدنا من مخططات بلاند و ألتمان توافقا جيد جدا بين ال tMPI و ال MPI Doppler، حيث بلغ متوسط الفرق -0.07 و تراوح الفرق المطلق بين -0.38 و0.24 و و كانت جميع القيم ضمن مجال الثقة 95%. و وجدنا كذلك علاقة طردية ضعيفة بين MPI Doppler وكل من RVSP (mmHg) (r=0.18، p=0.05) و TRV (m/s)( r=0.18، p=0.05) و علاقةعكسية ضعيفة مع TAPSE (mm) (r=-0.21، p=0.03). كما وجدنا علاقة طردية أقوى بين نسبيا بين tMPI وكل من RVSP (mmHg) (r=0.28، p=0.02) و TRV (m/s) (r=0.29، p=0.02). الخلاصة: لقد تبين من دراستنا أن مشعر تاي يمتلك علاقة جيدة مع ارتفاع الضغط الرئوي و يمكن أن يكشف سوء الوظيفة البطينية قبل تطور قصور القلب الأيمن الصريح، و يمكن للتقييم أن يتم بالطريقة النسيجية أو التقليدية مع وجود بعض الأفضلية للتصوير النسيجي. كما يشار كذلك إلى أن استخدام الطريقتين معا يزيد من قيمة المشعر.